Human Papillomavirus (HPV) in Oral Cavity Lesions: Comparison with Other Oral Cancer Risk Factors - Venezuela, Raúl Fernando (2013)
Fil: Venezuela, Raúl Fernando. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Instituto de Virología; Argentina